(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Tholodus schmidi, a rare marine reptile of debated affinity and with a peculiar durophagous dentition, is for the first time recorded outside the Muschelkalk Basin of Central Europe. Parts of a mandibular ramus and a maxilla, both bearing teeth and nearly uncrushed, have been found in the upper Anisian (Balatonicus Subzone) of northeastern Italy. The tooth implantation is relatively complex, with both "alveolate" and "ankylosed" teeth. Disarticulated postcranial bones of an ichthyosaur have been found close to, but not in articular association with, the dentigerous bones of Tholodus. The humerus resembles that of immature individuals of the Chinese genus Chaohusaurus. This association, and some features of teeth and dentigerous bones, suggests that Tholodus might be a grippiid ichthyosaur.